2016
DOI: 10.5511/plantbiotechnology.16.0706a
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the gene for F1–ATPase β subunit (<i>AtpB</i>) for the grain quality of rice matured in a high-temperature environment

Abstract: Rice grain filling is impaired by high-temperature stress during seed development. This event results in reduced grain yield and quality because of formation of smaller and chalky grains, and often causes problems in agriculture. Hightemperature stress causes disorders in primary metabolism pathways including ATP accumulation in the developing seeds. To determine the effect on the genes for ATP biosynthesis, we created the transformant rice plants in which expression of an F1-ATPase β subunit gene (AtpB) was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…High-temperature stress induces downregulation of the expression of several genes involved in starch biosynthesis, as well as those involved in sucrose import and degradation, resulting in insufficient ATP production in the sink organs (Yamakawa and Hakata 2010;Yamakawa et al 2007). We have shown that tolerance to high-temperature stress is acquired by overexpression of the gene for F1-ATPase β subunit (AtpB) in rice transformants, as evidenced by a significant increase in the ratio of perfect grains without any chalky part (Kusano et al 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…High-temperature stress induces downregulation of the expression of several genes involved in starch biosynthesis, as well as those involved in sucrose import and degradation, resulting in insufficient ATP production in the sink organs (Yamakawa and Hakata 2010;Yamakawa et al 2007). We have shown that tolerance to high-temperature stress is acquired by overexpression of the gene for F1-ATPase β subunit (AtpB) in rice transformants, as evidenced by a significant increase in the ratio of perfect grains without any chalky part (Kusano et al 2016).…”
mentioning
confidence: 99%
“…(A) Amount of the OsLEA5 transcript in the transformants. Total RNA was prepared from developing seeds (15 DAF) as described previously (Kusano et al 2016), and subjected to real time RT-PCR analysis using the Thunderbird kit (Toyobo, Osaka, Japan). Numbers with prefix # indicate the individual RNAi transformants.…”
mentioning
confidence: 99%
See 1 more Smart Citation